Comparison of the Data Classification Approaches to Diagnose Spinal Cord Injury - Demirer, Rüştü Murat; Arslan, Yunus Ziya; Palamar, Deniz; Uğur, Mukden; Karamehmetoğlu, Şafak Sahir (Hindawi Publishing Corporation, 410 Park Avenue, 15Th Floor, #287 Pmb, New York, Ny 10022 USA, 2012)
In our previous study, we have demonstrated that analyzing the skin impedancesmeasured along the key points of the dermatomes might be a useful supplementary technique to enhance the diagnosis of spinal cord injury (SCI), especially for unconscious and noncooperative patients. Initially, in order to distinguish between the skin impedances of control group and patients, artificial neural networks (ANNs) were used as the main data classification approach. However, in the present study, we have proposed two more data classification approaches, that is, support vector machine (SVM) and hierarchical cluster tree analysis (HCTA), which improved the classification rate and also the overall performance. A comparison of the performance of these three methods in classifying traumatic SCI patients and controls was presented. The classification results indicated that dendrogram analysis based on HCTA algorithm and SVM achieved higher recognition accuracies compared to ANN. HCTA and SVM algorithms improved the classification rate and also the overall performance of SCI diagnosis.
Keywords: support vector machine; networks; destek vektör makinesi; ağlar